Ternary composite nanofiber for marine metal corrosion prevention and electromagnetic wave absorption as well as preparation method and application of ternary composite nanofiber

The copper and cobalt metal ions are loaded through electrospinning technology and ternary composite nanofibers are prepared through high-temperature carbonization treatment, which solves the problem of easy corrosion of traditional electromagnetic wave absorbing materials in high humidity and acid-base environments, and achieves the efficient electromagnetic wave absorption and corrosion resistance of the materials.

CN119553393AActive Publication Date: 2025-03-04INST OF OCEANOLOGY - CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411507304.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-03-04
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

Traditional electromagnetic wave absorbing materials are prone to corrosion in high humidity and acid-base environments, resulting in reduced life and absorption efficiency, and their application in marine engineering is limited.

Method used

Electrospinning technology is used to load copper and cobalt metal ions into nanofibers, and ternary composite nanofibers (Cu/Co/C composite nanofibers) are prepared through high-temperature carbonization treatment. This material has electrical conductivity and magnetic properties, and can be carbonized under nitrogen protection, improving its conductivity and corrosion resistance.

Benefits of technology

The prepared ternary composite nanofiber not only has excellent electromagnetic wave absorption performance, but also has good acid and alkali resistance and salt spray corrosion resistance, and is suitable for applications in harsh environments such as the ocean.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553393A_ABST
    Figure CN119553393A_ABST
Patent Text Reader

Abstract

The invention provides a ternary composite nanofiber capable of being used for marine metal corrosion prevention and electromagnetic wave absorption and a preparation method and application of the ternary composite nanofiber. The preparation method of the ternary composite nanofiber comprises the following steps: (1) preparation of a precursor solution: dispersing a copper salt and a cobalt compound in a first solvent, stirring until the copper salt and the cobalt compound are fully dissolved, adding a polymer, and uniformly mixing to obtain the precursor solution; (2) preparation of a nanofiber membrane: performing electrostatic spinning on the precursor solution to obtain the nanofiber membrane loaded with copper and cobalt metal ions; and (3) carbonization: drying the nanofiber membrane, and performing high-temperature treatment after drying to obtain the ternary composite nanofiber capable of being used for marine metal corrosion prevention and electromagnetic wave absorption. The preparation method of the ternary composite nanofiber is simple and low in cost, and the prepared ternary composite nanofiber has a huge application prospect when being used for electromagnetic wave shielding in corrosion environments such as ocean.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of marine metal anti-corrosion, and specifically relates to a ternary composite nanofiber that can be used for marine metal anti-corrosion and electromagnetic wave absorption, and a preparation method and application thereof. Background Art

[0002] Excellent electromagnetic wave absorbing materials should have high absorption capacity and anti-corrosion ability, which is of great significance to military stealth technology and elimination of electromagnetic interference, especially to be able to serve in high humidity environment and acid-base environment. However, the development and application of traditional absorbing materials are limited by factors such as high density, high matching thickness and single loss mechanism. Once the electromagnetic wave absorbing material is damaged by corrosion, its life and absorption efficiency will be greatly reduced.

[0003] Seawater contains a variety of inorganic salts, which can damage the performance of electromagnetic wave absorbing materials. Electromagnetic wave absorbing materials are generally used on the surface of metal substrates. Therefore, if the electromagnetic wave absorbing material has anti-corrosion properties, it can not only improve its application as an electromagnetic wave absorbing material in corrosive environments such as marine engineering, but also be used for the anti-corrosion of metal substrates in marine engineering, thereby broadening the application scope of electromagnetic wave absorbing materials.

[0004] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention

[0005] The purpose of the present invention is to provide a ternary composite nanofiber that can be used for marine metal corrosion protection and electromagnetic wave absorption, and its preparation method and application, so as to help make the electromagnetic wave absorbing material have anti-corrosion properties and broaden its application in marine engineering.

[0006] In order to achieve the above-mentioned purpose, the present invention provides the following technical scheme: a method for preparing a ternary composite nanofiber that can be used for marine metal corrosion protection and electromagnetic wave absorption, comprising the following steps: (1) preparation of a precursor solution: dispersing a copper salt and a cobalt compound in a first solvent, stirring until fully dissolved, adding a polymer, and mixing evenly to obtain the precursor solution; (2) preparation of a nanofiber membrane: electrospinning the precursor solution to obtain a nanofiber membrane loaded with copper and cobalt metal ions; (3) carbonization: drying the nanofiber membrane and subjecting it to high-temperature treatment after drying to obtain the ternary composite nanofiber that can be used for marine metal corrosion protection and electromagnetic wave absorption; the high-temperature treatment comprises a first stage and a second stage; the first stage: heating from room temperature to 200-250°C in an air atmosphere and keeping warm for 1.5-2h; the second stage: continuing to heat to 700-800°C in a nitrogen and / or rare gas atmosphere and keeping warm for 1.5-2h.

[0007] Preferably, the molar ratio of the copper salt to the cobalt compound is 1:(0.9-1.1), and the mass ratio of the polymer to the solvent is 3:(47-53).

[0008] Preferably, the copper salt is copper acetate, the cobalt compound is cobalt acetylacetonate; the first solvent is DMF; the polymer is polyacrylonitrile; and the mass ratio of copper acetate to DMF is (5-10):100.

[0009] Preferably, in step (2), during the electrospinning, the distance between the electrospinning needle and the receiver is 14-15 cm, the working voltage is set to 8-12 kV, the injection speed is 0.01-0.03 mm / min, and the air humidity is 25%-30%.

[0010] Preferably, in step (3), the drying temperature is 60-70°C, and the drying time is 12-24h; and the heating rate of the second stage is 5-7°C / min.

[0011] The present invention also provides a ternary composite nanofiber that can be used for marine metal corrosion protection and electromagnetic wave absorption, which adopts the following technical scheme: a ternary composite nanofiber that can be used for marine metal corrosion protection and electromagnetic wave absorption, and the ternary composite nanofiber that can be used for marine metal corrosion protection and electromagnetic wave absorption is prepared by the method as described above.

[0012] The present invention also provides a coating that can be used for marine metal corrosion protection and electromagnetic wave absorption, which adopts the following technical scheme: a coating that can be used for marine metal corrosion protection and electromagnetic wave absorption, comprising a resin, a curing agent, a second solvent and the ternary composite nanofiber that can be used for marine metal corrosion protection and electromagnetic wave absorption as described above.

[0013] Preferably, the resin is epoxy resin, the curing agent is polyamide curing agent, and the mass ratio of the epoxy resin to the polyamide curing agent is 1:(0.5-1.2); the second solvent is ethanol, and the mass ratio of the epoxy resin to the ethanol is 1:(1.5-2.1); the mass ratio of the ternary composite nanofiber that can be used for marine metal corrosion protection and electromagnetic wave absorption to the epoxy resin is 1%-5%.

[0014] The present invention also provides a coating that can be used for marine metal corrosion protection and electromagnetic wave absorption, which adopts the following technical solution: a coating that can be used for marine metal corrosion protection and electromagnetic wave absorption, the coating is formed by drying the coating as described above.

[0015] The present invention also provides a marine engineering component with dual functions of corrosion resistance and electromagnetic wave absorption, which adopts the following technical scheme: a marine engineering component with dual functions of corrosion resistance and electromagnetic wave absorption, comprising a metal substrate, the surface of which is loaded with the coating described above.

[0016] Beneficial effects:

[0017] The present invention successfully loads conductive metal copper and magnetic metal cobalt into nanofibers through electrostatic spinning technology, and then carbonizes the composite nanofibers by a post-treatment technology of high-temperature carbonization of the nanofiber membrane obtained by electrostatic spinning under nitrogen protection, so as to prepare the ternary composite nanofibers (i.e., Cu / Co / C composite nanofibers) of the present invention that can be used for marine metal corrosion protection and electromagnetic wave absorption. Among them, by subjecting the nanofiber membrane to high-temperature carbonization treatment under a nitrogen environment, it is helpful to further improve its electrical conductivity and enhance its electromagnetic wave absorption performance, and the chemical stability of the ternary composite nanofibers (i.e., Cu / Co / C composite nanofibers) obtained after carbonization is greatly improved, and has excellent corrosion resistance (e.g., acid and alkali corrosion resistance or salt spray corrosion resistance).

[0018] In addition, the present invention successfully loads metal particles on nanofibers through blending technology, which solves the shortcomings of nanofibers prepared by electrospinning technology, such as poor conductivity and single loss mechanism. The preparation process is simple and controllable, low cost, and the prepared ternary composite nanofibers have excellent electromagnetic wave absorption effect. In the field of electromagnetic wave absorption, especially for electromagnetic wave shielding in corrosive environments such as oceans, it has great application prospects.

[0019] In the coating of the present invention, the ternary composite nanofibers can perfectly match the epoxy resin and can effectively fill the inherent defects of the organic coating, which can not only improve the overall flexibility of the coating, but also fill the micropore defects in the coating, cut off the penetration path of corrosive ions, and delay the occurrence of the corrosion process.

[0020] The ternary composite nanofiber of the present invention has a wide range of applications, is compatible with epoxy resin, has excellent electromagnetic wave absorption and corrosion resistance effects after being cured into a coating, and can be adapted to electromagnetic wave absorption work in corrosive environments such as the ocean. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:

[0022] Figure 1 are transmission electron microscope images; among them, (a) is the transmission electron microscope image of the ternary composite nanofiber that can be used for marine metal corrosion protection and electromagnetic wave absorption of Example 1 (800°C), (b) is the transmission electron microscope image of the composite nanofiber of Comparative Example 1 (600°C), and (c) is the transmission electron microscope image of the ternary composite nanofiber that can be used for marine metal corrosion protection and electromagnetic wave absorption of Example 3 (700°C).

[0023] Figure 2 1 and 2 are Raman graphs of the composite nanofibers of Example 1, Comparative Example 1 and Example 3 of the present invention.

[0024] Figure 3 1 and 2 are XRD diagrams of the composite nanofibers of Example 1, Comparative Example 1 and Example 3 of the present invention.

[0025] Figure 4 In the figure, (a) is the hysteresis loop diagram of Example 1, Example 3 and Comparative Example 1, and (b) is a partial enlarged diagram of (a).

[0026] Figure 5 are reflection loss diagrams; wherein, (a) is the reflection loss diagram of the composite nanofiber of comparative example 1, (b) is the reflection loss diagram of the ternary composite nanofiber that can be used for marine metal corrosion protection and electromagnetic wave absorption of embodiment 3, and (c) is the reflection loss diagram of the ternary composite nanofiber that can be used for marine metal corrosion protection and electromagnetic wave absorption of embodiment 1.

[0027] Figure 6 The figures are the results of acid and alkali resistance test and salt spray test; wherein, (a) is a photograph of the Cu / Co / C composite nanofibers of Example 1 immersed in 3mmol / L NaOH solution, 3mmol / L HNO3 solution, ice water and room temperature water (the "supersonic" in the figure means that the fibers were also subjected to ultrasonic treatment for 20 minutes when immersed in room temperature water) for 72 hours; (b) is a photograph of the Cu / Co / C composite nanofibers of Example 1 immersed in 3mmol / L NaOH solution, 3mmol / L HNO3 solution, ice water and room temperature water (the "supersonic" in the figure means that the fibers were also subjected to ultrasonic treatment for 20 minutes when immersed in room temperature water) for 15 days (in (b), the arrangement order of the four solutions is the same as that of (a)); (c) is a photograph of the coatings of Example 1, Example 4, Example 5 and Comparative Example 2 of the present invention before and after the salt spray test.

[0028] Figure 7 The figures are graphs showing the results of electrochemical impedance tests; wherein (a) is the Nyquist plot of the coatings of Example 1 (5%), Example 4 (3%), Example 5 (1%) and Comparative Example 2 (EP) after 60 days of salt spray testing; and (b) is a partial enlarged view of (a). DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0030] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0031] The present invention aims to solve the problem that electromagnetic wave absorbing materials need to serve in an environment prone to corrosion such as high humidity and high salt when applied to marine engineering. The present invention provides a method for preparing a ternary composite nanofiber that can be used for marine engineering metal corrosion protection and electromagnetic wave absorption. The ternary composite nanofiber that can be used for marine engineering metal corrosion protection and electromagnetic wave absorption prepared by the method has anti-corrosion properties and is suitable for application in marine engineering.

[0032] The method for preparing a ternary composite nanofiber that can be used for marine metal corrosion protection and electromagnetic wave absorption according to an embodiment of the present invention comprises the following steps: (1) preparation of a precursor solution: dispersing a copper salt and a cobalt compound in a first solvent, stirring until fully dissolved, adding a polymer, and mixing evenly to obtain a precursor solution; (2) preparation of a nanofiber membrane: electrospinning the precursor solution to obtain a nanofiber membrane loaded with copper and cobalt metal ions; (3) drying the nanofiber membrane and subjecting it to high-temperature treatment after drying to obtain an electromagnetic wave absorption material that can be used for marine metal corrosion protection; the high-temperature treatment comprises a first stage and a second stage; the first stage (pre-oxidation): heating from room temperature to 200-250°C (for example, 200°C, 210°C, 220°C, 230°C, 240°C or 250°C) in an air atmosphere, and keeping warm for 1.5-2h (for example, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2h). The second stage (carbonization): in a nitrogen or rare gas (e.g., helium) atmosphere, continue heating to 700-800°C (e.g., 700°C, 720°C, 740°C, 760°C, 780°C, or 800°C), and keep warm for 1.5-2h (e.g., 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, or 2h). The first stage (pre-oxidation) of high temperature treatment can partially oxidize elements such as hydrogen, oxygen, and nitrogen in the polymer fiber to form oxides with a high oxygen content, thereby reducing the amount of gas released during carbonization of the ternary composite nanofiber (i.e., Cu / Co / C composite nanofiber), reducing the internal stress during carbonization of the fiber and the thermal shrinkage of the fiber, thereby improving the carbonization efficiency; the purpose of the second stage (carbonization) of high temperature treatment is to increase the mechanical strength and thermal stability of the ternary composite nanofiber (i.e., Cu / Co / C composite nanofiber) so that it can be used under high temperature and high strength conditions. By controlling the temperature and time of carbonization, the thermal stability, density and crystallinity of the fiber can be controlled to obtain carbon fiber with microwave absorption performance. If the carbonization temperature deviates, the microwave absorption performance of the material may decrease.

[0033] Electrospinning technology is an effective method for preparing fibrous polymer materials, and has the advantages of easy operation, short preparation cycle, and the ability to collect a large number of continuous long fibers. By changing the parameters, ultrafine fibers with diameters between nanometers and microns can be prepared. The unique interconnected fiber structure gives it a high porosity, meeting the various requirements of composite fibers. Specific components can be compounded into nanofibers through blending technology to prepare a variety of composite materials. The present invention successfully loads conductive metal copper and magnetic metal cobalt into nanofibers through electrospinning technology, and then carbonizes the composite nanofibers through a post-treatment technology of high-temperature carbonization of the nanofiber membrane obtained by electrospinning under the protection of nitrogen or rare gas, to prepare the ternary composite nanofibers (i.e., Cu / Co / C composite nanofibers) of the present invention that can be used for marine metal corrosion protection and electromagnetic wave absorption. Among them, high-temperature carbonization treatment of the nanofiber membrane in a nitrogen environment helps to further improve its conductivity and enhance its electromagnetic wave absorption performance. The chemical stability of the ternary composite nanofiber (i.e., Cu / Co / C composite nanofiber) obtained after carbonization is greatly improved, and it has excellent corrosion resistance (for example, acid and alkali corrosion resistance or salt spray corrosion resistance).

[0034] In addition, the present invention successfully loads metal particles on nanofibers through blending technology, which solves the shortcomings of poor conductivity and single loss mechanism of nanofibers prepared by electrospinning technology. The preparation process is simple and controllable with low cost. The prepared composite nanofibers have excellent electromagnetic wave absorption effect and have great application prospects in the field of electromagnetic wave absorption.

[0035] The preparation method of the ternary composite nanofibers for marine metal corrosion protection and electromagnetic wave absorption of the present invention is simple and low-cost, and the prepared ternary composite nanofibers have great application prospects for electromagnetic wave shielding in corrosive environments such as the ocean.

[0036] In a preferred embodiment of the method for preparing ternary composite nanofibers for marine metal corrosion protection and electromagnetic wave absorption of the present invention, the molar ratio of copper salt to cobalt compound is 1:(0.9-1.1) (for example, 1:0.9, 1:0.95, 1:1, 1:1.05 or 1:1.1). If the molar ratio of copper to cobalt is changed, the microscopic morphology, electromagnetic parameters (dielectric constant, magnetic permeability), absorption bandwidth and impedance matching of the material will change, thereby affecting the wave absorption effect. The mass ratio of polyacrylonitrile to the first solvent is 3:(47-53) (for example, 3:47, 3:48, 3:49, 3:50, 3:51, 3:52 or 3:53; preferably, when the mass ratio of polyacrylonitrile to the first solvent is 3:50, the electrostatic spinning morphology effect is the best).

[0037] In a preferred embodiment of the method for preparing ternary composite nanofibers for marine metal corrosion protection and electromagnetic wave absorption of the present invention, the copper salt is copper acetate, the cobalt compound is cobalt acetylacetonate; the first solvent is DMF; the polymer is polyacrylonitrile; the mass ratio of copper acetate to DMF is (5-10):100 (for example, 5:100, 6:100, 7:100, 8:100, 9:100 or 10:100). Among them, DMF is a good solvent that can fully dissolve polyacrylonitrile.

[0038] In a preferred embodiment of the method for preparing ternary composite nanofibers for marine metal corrosion protection and electromagnetic wave absorption of the present invention, in step (2), during electrospinning, the distance between the electrospinning needle and the receiver is 14-15 cm (e.g., 14 cm, 14.3 cm, 14.6 cm, 14.8 cm or 15 cm), the working voltage is set to 8-12 kV (e.g., 8 kV, 9 kV, 10 kV, 11 kV or 12 kV), the injection speed is 0.01-0.03 mm / min (e.g., 0.01 mm / min, 0.015 mm / min, 0.02 mm / min, 0.025 mm / min or 0.03 mm / min), and the air humidity is 25%-30% (e.g., 25%, 26%, 27%, 28%, 29% or 30%). Changes in the above parameters will result in the diameter, morphology and structure of the filaments, thereby affecting the wave absorption performance of the product.

[0039] In a preferred embodiment of the method for preparing ternary composite nanofibers for marine metal corrosion protection and electromagnetic wave absorption of the present invention, in step (3), the drying temperature is 60°C-70°C (for example, 60°C, 62°C, 64°C, 66°C, 68°C or 70°C), and the drying time is 12-24h (for example, 12h, 16h, 20h or 24h); the heating rate in the second stage is 5-7°C / min (for example, 5°C / min, 6°C / min or 7°C / min). It should be noted that a heating rate that is too fast or too slow will affect the grain size, carbon content and precipitation properties of the material (a heating rate that is too fast will lead to uneven carbonization; a heating rate that is too slow will lead to uneven microscopic changes in the material, thereby affecting the wave absorption performance).

[0040] The present invention also proposes a ternary composite nanofiber that can be used for marine metal corrosion protection and electromagnetic wave absorption. The ternary composite nanofiber that can be used for marine metal corrosion protection and electromagnetic wave absorption in an embodiment of the present invention is prepared by the method described above.

[0041] The present invention also proposes a coating that can be used for marine metal corrosion protection and electromagnetic wave absorption. The coating that can be used for marine metal corrosion protection and electromagnetic wave absorption in an embodiment of the present invention includes a resin, a curing agent, a second solvent and the ternary composite nanofiber that can be used for marine metal corrosion protection and electromagnetic wave absorption as described above.

[0042] The coating formed by the coating for marine metal corrosion protection and electromagnetic wave absorption after drying has electromagnetic wave absorption performance and excellent corrosion resistance.

[0043] In a preferred embodiment of the coating that can be used for marine metal corrosion protection and electromagnetic wave absorption of the present invention, the resin is epoxy resin, the curing agent is polyamide curing agent, and the mass ratio of epoxy resin to polyamide curing agent is 1:(0.5-1.2) (for example, 1:0.5, 1:0.7, 1:0.8, 1:1 or 1:1.2); the second solvent is ethanol, and the mass ratio of epoxy resin to ethanol is 1:(1.5-2.1) (for example, 1:1.5, 1:1.7, 1:1.9, 1:2 or 1:2.1); the mass ratio of ternary composite nanofibers that can be used for marine metal corrosion protection and electromagnetic wave absorption to epoxy resin is 1%-5% (for example, 1%, 2%, 3%, 4% or 5%).

[0044] In the coating of the present invention, the ternary composite nanofibers can perfectly match the epoxy resin and can effectively fill the inherent defects of the organic coating, which can not only improve the overall flexibility of the coating, but also fill the micropore defects in the coating, cut off the penetration path of corrosive ions, and delay the occurrence of the corrosion process.

[0045] The ternary composite nanofiber of the present invention has a wide range of applications, is compatible with epoxy resin, has excellent electromagnetic wave absorption and corrosion resistance effects after being cured into a coating, and can be adapted to electromagnetic wave absorption work in a corrosive environment.

[0046] The present invention also proposes a coating that can be used for marine metal corrosion protection and electromagnetic wave absorption. The coating that can be used for marine metal corrosion protection and electromagnetic wave absorption in an embodiment of the present invention is formed by drying the coating as described above.

[0047] Preferably, the thickness of the coating that can be used for marine metal corrosion protection and electromagnetic wave absorption in the embodiment of the present invention is 80-130 μm (for example, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm or 130 μm).

[0048] The present invention also proposes a marine engineering component with dual functions of corrosion protection and electromagnetic wave absorption. The marine engineering component with dual functions of corrosion protection and electromagnetic wave absorption of the embodiment of the present invention includes a metal substrate, and the surface of the metal substrate is loaded with the coating as described above, which improves the corrosion resistance while maintaining the wave absorbing performance. For example, in areas such as tropical marine climates, the radar absorbing coatings of modern air force weapons are very susceptible to corrosion due to environmental influences. How to improve the corrosion resistance of the material while ensuring its wave absorbing performance has become a hot issue. The coating that can be used for marine metal corrosion protection and electromagnetic wave absorption of the present invention helps to solve or improve the equipment that needs to use radar absorbing coatings in tropical marine climate areas.

[0049] Preferably, the metal substrate may be carbon steel (eg, Q235).

[0050] The ternary composite nanofibers for marine metal corrosion protection and electromagnetic wave absorption of the present invention and their preparation method and application are described in detail below through specific examples.

[0051] In the following examples, the epoxy resin used is E-44 (6101) epoxy resin produced by Zhenjiang Danbao Resin Co., Ltd.; the curing agent is 650 low molecular weight polyamide curing agent produced by Dingyuan County Danbao Resin Co., Ltd.

[0052] Example 1

[0053] The ternary composite nanofibers of this embodiment that can be used for marine metal corrosion protection and electromagnetic wave absorption are prepared by a method comprising the following steps:

[0054] (1) Preparation of electrospinning precursor solution

[0055] 1.4 g of copper acetate and 1.8 g of cobalt acetylacetonate powder were weighed and dissolved in 20 g of N,N-dimethylformamide solution. After uniform stirring, 1.2 g of polyacrylonitrile was added thereto. After stirring at room temperature (25° C.) for 12 h, a dark green spinning solution was obtained.

[0056] (2) Preparation of nanofiber membranes

[0057] The spinning solution obtained in step (1) was injected into a 10 mL plastic syringe, and the spinning needle was connected to the positive electrode after fixing. A piece of aluminum foil was covered on the collector, and electrospinning was performed, and the distance between the positive and negative electrodes was adjusted to 14 cm. The electrospinning working voltage was 12 kV, the injection speed was 0.02 mm / min, the temperature was 25° C., and the humidity was 27%; the spinning time was 12 h, and a nanofiber membrane loaded with Cu and Co metal ions was obtained.

[0058] (3) Carbonization

[0059] The nanofiber membrane was removed from the electrospinning machine and placed in a constant temperature drying oven together with the aluminum foil at 70°C for 12 hours; the nanofiber membrane was torn off the aluminum foil and placed in a magnetic boat, and heated in a tubular furnace under nitrogen protection:

[0060] The first stage: heating from room temperature to 200°C in air atmosphere, keeping warm for 1 hour;

[0061] The second stage: in a nitrogen atmosphere, heating to 800°C at a rate of 5°C / min and keeping warm for 2 hours; finally, a black fiber is obtained, which is the ternary composite nanofiber (Cu / Co / C composite nanofiber) of this embodiment that can be used for marine metal corrosion protection and electromagnetic wave absorption.

[0062] The coating that can be used for marine metal corrosion protection and electromagnetic wave absorption in this embodiment includes 1g of epoxy resin (water-based epoxy resin), 0.8g of curing agent, 2mL of ethanol and 0.05g of ternary composite nanofibers (Cu / Co / C composite nanofibers) that can be used for marine metal corrosion protection and electromagnetic wave absorption in this embodiment.

[0063] The coating for marine metal corrosion protection and electromagnetic wave absorption of this embodiment is prepared by dissolving 1g of epoxy resin (water-based epoxy resin) and 0.8g of curing agent in 2mL of anhydrous ethanol, stirring evenly and mixing with 0.05g of Cu / Co / C composite nanofibers.

[0064] The coating for marine metal corrosion protection and electromagnetic wave absorption of this embodiment: the coating for marine metal corrosion protection and electromagnetic wave absorption as described above is evenly coated on the metal substrate, and dried to make the coating reach a surface dry state, thereby obtaining the coating for marine metal corrosion protection and electromagnetic wave absorption of this embodiment. In this embodiment, the thickness of the final coating is 80 μm.

[0065] Example 2

[0066] The only difference between this embodiment and embodiment 1 is that the water-based epoxy resin and the low molecular weight polyamide curing agent are mixed in a mass ratio of 5:4, and the ternary composite nanofibers prepared in embodiment 1 that can be used for marine metal corrosion protection and electromagnetic wave absorption are added (the mass is 5% of the water-based epoxy resin) to obtain the coating that can be used for marine metal corrosion protection and electromagnetic wave absorption in this embodiment.

[0067] The coating that can be used for marine metal corrosion protection and electromagnetic wave absorption of this embodiment: the coating as described above is evenly coated on the metal substrate (Q235 carbon steel) with a glass rod, brushed three times, and then placed in an oven at 60°C for 20 minutes. When the coating reaches a surface dry state, the coating that can be used for marine metal corrosion protection and electromagnetic wave absorption of this embodiment is obtained (the thickness of the coating that can be used for marine metal corrosion protection and electromagnetic wave absorption of this embodiment is 100μm).

[0068] Example 3

[0069] The ternary composite nanofibers for marine metal corrosion protection and electromagnetic wave absorption of this embodiment are different from those of Example 1 only in that in step (3), the temperature is heated to 700° C. during the second stage of carbonization; the rest are consistent with Example 1.

[0070] Example 4

[0071] The coating for marine metal corrosion protection and electromagnetic wave absorption in this comparative example is different from that in Example 2 only in that the mass of the ternary composite nanofibers for marine metal corrosion protection and electromagnetic wave absorption in the coating is 3% of the water-based epoxy resin; the rest is consistent with Example 2.

[0072] Example 5

[0073] The coating for marine metal corrosion protection and electromagnetic wave absorption of this embodiment is different from that of Example 2 only in that the mass of the ternary composite nanofibers for marine metal corrosion protection and electromagnetic wave absorption in the coating is 1% of the water-based epoxy resin; the rest is consistent with Example 2.

[0074] Comparative Example 1

[0075] The composite nanofibers of this comparative example differ from those of Example 1 only in that in step (3), the temperature is heated to 600° C. during the second stage of carbonization; the rest are the same as those of Example 1.

[0076] Comparative Example 2

[0077] The coating of this comparative example is different from that of Example 1 only in that the ternary composite nanofibers prepared in Example 1 and used for marine metal corrosion protection and electromagnetic wave absorption are not added to the coating; the rest are consistent with Example 2.

[0078] Experimental example

[0079] 1. The performance of the ternary composite nanofibers prepared in Example 1 and Comparative Examples 1 and 2 and used for marine metal corrosion protection and electromagnetic wave absorption was tested:

[0080] 1) Transmission electron microscopy (TEM)

[0081] Each sample was observed under a transmission electron microscope ( Figure 1 ).in, Figure 1 (a) is a composite nanofiber formed at a carbonization temperature of 800°C (Example 1), and the fiber diameter is about 90 nm; Figure 1 (b) is a composite nanofiber formed at a carbonization temperature of 600°C (Comparative Example 1), and the fiber diameter is about 150 nm; Figure 1(c) shows the composite nanofiber formed at a carbonization temperature of 700°C (Example 3). As can be seen from the figure, the fiber diameter is about 150 nm.

[0082] 2) Raman

[0083] Raman spectra of Cu / Co / C composite nanofibers Figure 2 As shown; among them, 1340cm -1 The D peak at 1580 cm -1 The G peaks of the D and G peaks are used to represent amorphous carbon and graphite carbon, respectively, and the peak intensity ratio of the D and G peaks (I D / I G ) can be used to evaluate the degree of graphitization of carbon. The smaller the ratio, the higher the degree of graphitization. Figure 2 The peak ratios of the composite nanofibers formed at carbonization temperatures of 600°C (Comparative Example 1), 700°C (Example 3), and 800°C (Example 1) are quantitatively calculated to be 1.37, 1.1, and 1.03, respectively.

[0084] It can be seen that with the increase of carbonization temperature (carbonization temperature of the second stage), I D / I G The value gradually decreases, and the carbonization degree of the composite nanofibers gradually increases.

[0085] 3) X-ray diffraction spectrum (XRD)

[0086] Figure 3 The XRD spectra of the composite nanofibers obtained in Example 1 (800°C), Comparative Example 1 (600°C) and Example 3 (700°C) show that, as the carbonization temperature increases, the crystallinity of Cu and Co on the fibers gradually increases.

[0087] 4) Magnetic strength test

[0088] The hysteresis loops of the three samples of Example 1, Example 3 and Comparative Example 1 were tested by VSM at room temperature under a ±2T magnetic field. Figure 4 shown.

[0089] Both Example 3 and Example 1 exhibit typical moderate ferromagnetism, while Comparative Example 1 (600°C) still exhibits an unsaturated magnetization state under a 2T magnetic field, indicating the presence of paramagnetic components in the sample. This result shows that the composite nanofibers formed in Comparative Example 1 are not completely carbonized and decomposed. The saturation magnetization values ​​of the three samples with carbonization temperatures of 600°C (Comparative Example 1), 700°C (Example 3) and 800°C (Example 1) are 16.4emu / g, 9.2emu / g and 5.1emu / g, respectively. As the carbonization temperature increases, the proportion of non-magnetic components in the composite fibers increases, and the mass percentage of magnetic Co decreases, resulting in a gradual downward trend in the saturation magnetization value of the material, indicating that the sample has lower magnetic permeability and magnetic loss capacity. The coercive forces of the three samples with carbonization temperatures of 600°C, 700°C and 800°C are 50Oe, 37.5Oe and 34.1Oe respectively, which are higher than the coercive force of cobalt (~10Oe). This significant improvement is due to the size effect and the enhancement of the surface anisotropic field. A higher coercive force is conducive to obtaining a relatively high natural resonance frequency. The enhancement of the coercive force will move the resonance peak from MHz to GHz, which ensures the absorption of electromagnetic waves in the research frequency band.

[0090] 5) Electromagnetic wave reflection loss test

[0091] The reflection loss of Example 1, Comparative Example 1 and Example 3 in the frequency range of 2-18 GHz was analyzed. Figure 5 RL curves of electromagnetic wave absorbing materials prepared by mixing 20 wt % of different samples with 80 wt % of paraffin wax. The thickness of each sample is set to 1-5 mm.

[0092] Quantitative analysis shows that the three-dimensional RL value of the composite nanofiber prepared in Comparative Example 1 ( Figure 5 (a)) are almost all greater than -10dB within the test range, which indicates that the composite nanofibers prepared at a carbonization temperature of 600℃ cannot meet the requirements of electromagnetic wave absorption.

[0093] Figure 5 (b) and (c) are the three-dimensional RL value curves of Example 3 (carbonization temperature 700°C) and Example 1 (carbonization temperature 800°C), respectively. The two samples can effectively absorb electromagnetic waves. The RL value of Example 3 (carbonization temperature 700°C) at 17.12 GHz is min The value is -33.9dB, the matching thickness is only 1.3mm, and the maximum absorption bandwidth is 6.37GHz (11.6-18GHz) when the sample thickness is 1.5mm (RL≤10dB, 90% of the electromagnetic waves are absorbed); Example 1 (carbonization temperature 800℃) at 8GHz RL minThe value is -44.74 dB, and the matching thickness is only 2.7 mm. Example 1 (carbonization temperature 800° C.) has a maximum absorption bandwidth of 6.8 GHz (11.2-18 GHz) when the thickness is 1.5 mm.

[0094] The results show that the RL min The value is the smallest among the three samples. It has the advantages of strong absorption, thin matching thickness, and wide absorption bandwidth. It is a good electromagnetic absorption material.

[0095] 2. The corrosion resistance of the coatings for marine metal corrosion protection and electromagnetic wave absorption of Examples 1, 4 and 5 and the coating prepared in Comparative Example 2 was tested:

[0096] 1) Acid and alkali resistance test

[0097] The Cu / Co / C composite nanofibers of Example 1 were immersed in 3 mmol / L NaOH solution, 3 mmol / L HNO3 solution, ice water and room temperature water (ultrasound treatment was also performed for 20 min when immersed in room temperature water) for 72 h. After the immersion, each solution remained transparent (see Figure 6 (a)), indicating that the Cu / Co / C composite nanofibers of the present invention have excellent mechanical properties.

[0098] The Cu / Co / C composite nanofibers of Example 1 were immersed in 3mmol / L NaOH solution, 3mmol / L HNO3 solution, ice water and room temperature water (ultrasound treatment was also performed for 20min when immersed in room temperature water) for 15 days (see Figure 6 (b); Figure 6 In (b), the arrangement order of the four solutions is the same as in (a). After immersion for 15 days, there is no visible change in the solution, which proves that the Cu / Co / C composite nanofibers can still have an absorbing effect after corrosion, indicating that the Cu / Co / C composite nanofibers have excellent acid and alkali resistance and corrosion resistance.

[0099] 2) Salt spray test

[0100] The coatings for marine metal corrosion protection and electromagnetic wave absorption of Example 1 (5%), Example 4 (3%) and Example 5 (1%) and the coating of Comparative Example 2 (pure epoxy) were respectively coated on metal substrates, and the coating thickness was controlled at 130 μm (±10 μm). A neutral salt spray test was carried out in a salt spray chamber (Japan SUGA cep-90) to evaluate the corrosion resistance of different samples.

[0101] The culture medium of the salt spray test is 5wt% NaCl solution, pH is 6.5-7.2, the test temperature is (35±2)°C, the spray pressure is between 0.1MPa and 0.15MPa, and the inlet pressure is between 0.2MPa and 0.4MPa.

[0102] After 60 days of salt spray testing, all samples still maintained their intact surfaces ( Figure 6 (c)).

[0103] 3) Electrochemical test

[0104] In order to further test the corrosion resistance of the sample, the coating (coating thickness: 130 μm) after 60 days of salt spray test was subjected to electrochemical test in 3.5 wt % NaCl solution, and the exposure time was 144 h.

[0105] The EIS results were obtained on an Autolab-PGSTAT302N electrochemical workstation using a three-electrode cell system with a coated steel block as the working electrode, a platinum plate electrode as the auxiliary electrode, and a saturated calomel electrode as the reference electrode. -2 ~10 5 The EIS data were tested in the Hz range with a root mean square amplitude of 10 mV. To ensure the reliability and repeatability of the EIS data, at least three measurements were performed on the blank coating and the composite coating.

[0106] Test results such as Figure 7 As shown in the figure, with the increase of the addition amount of the ternary composite nanofibers that can be used for marine metal corrosion protection and electromagnetic wave absorption, the radius gradually increases. When the addition amount of the ternary composite nanofibers that can be used for marine metal corrosion protection and electromagnetic wave absorption is 3% (Example 4) and 5% (Example 1), the capacitive reactance arc of the coating is similar, which is much greater than when the addition amount of the ternary composite nanofibers that can be used for marine metal corrosion protection and electromagnetic wave absorption is 0 (Comparative Example 2, Figure 7 The coatings of Example 5 and Example 5 also have an impedance improvement of 1-2 orders of magnitude relative to that of the coating of Comparative Example 1, indicating that in the coating, increasing the amount of the ternary composite nanofibers that can be used for marine metal corrosion protection and electromagnetic wave absorption of the present invention is beneficial to enhancing the corrosion resistance of the coating.

[0107] In combination with the above 1)-3), it can be known that the present invention can significantly increase the impedance of the coating and improve the corrosion resistance of the coating by adding ternary composite nanofibers that can be used for marine metal corrosion protection and electromagnetic wave absorption into the coating.

[0108] In summary, the present invention successfully prepared lightweight, wide absorption bandwidth, and corrosion-resistant Cu / Co / C ternary composite nanofibers by combining electrospinning with high-temperature carbonization treatment. Thanks to the unique fiber structure, the synergistic effect of multiple loss mechanisms, good impedance matching and high attenuation capability, the ternary composite nanofibers (Cu / Co / C ternary composite nanofibers) of the present invention that can be used for marine metal corrosion protection and electromagnetic wave absorption show excellent electromagnetic wave absorption effect. The size of the Cu / Co / C ternary composite nanofibers, the degree of crystallization of the agglomerates, the degree of graphitization, the matching thickness, the EAB and the RL value can be adjusted by the carbonization temperature. In addition, the coating containing the Cu / Co / C ternary composite nanofibers also has good corrosion resistance. The research results show that the Cu / Co / C ternary composite nanofiber is an excellent electromagnetic absorption material and has the ability to work in harsh environments such as humidity, acid and alkali, and low temperature.

[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing ternary composite nanofibers that can be used for marine metal corrosion protection and electromagnetic wave absorption, characterized in that: The steps include: (1) Preparation of a precursor solution: dispersing a copper salt and a cobalt compound in a first solvent, stirring until fully dissolved, adding a polymer, and mixing uniformly to obtain the precursor solution; (2) Preparation of nanofiber membrane: electrospinning the precursor solution to obtain a nanofiber membrane loaded with copper and cobalt metal ions; (3) Carbonization: drying the nanofiber membrane and subjecting it to high temperature treatment after drying to obtain the ternary composite nanofiber that can be used for marine metal corrosion protection and electromagnetic wave absorption; The high temperature treatment includes a first stage and a second stage; The first stage: in air atmosphere, heating from room temperature to 200-250℃, keeping warm for 1.5-2h; The second stage: In a nitrogen and / or rare gas atmosphere, continue heating to 700-800°C and keep warm for 1.5-2h.

2. The method for preparing the ternary composite nanofibers for marine metal corrosion protection and electromagnetic wave absorption as claimed in claim 1, characterized in that: The molar ratio of the copper salt to the cobalt compound is 1:(0.9-1.1), and the mass ratio of the polymer to the solvent is 3:(47-53).

3. The method for preparing the ternary composite nanofibers for marine metal corrosion protection and electromagnetic wave absorption as claimed in claim 1, characterized in that: The copper salt is copper acetate, and the cobalt compound is cobalt acetylacetonate; The first solvent is DMF; The polymer is polyacrylonitrile; The mass ratio of the cupric acetate to DMF is (5-10):

100.

4. The method for preparing the ternary composite nanofibers for marine metal corrosion protection and electromagnetic wave absorption as claimed in claim 1, characterized in that: In step (2), during the electrospinning, the distance between the electrospinning needle and the receiver is 14-15 cm, the working voltage is set to 8-12 kV, the injection speed is 0.01-0.03 mm / min, and the air humidity is 25%-30%.

5. The method for preparing the ternary composite nanofibers for marine metal corrosion protection and electromagnetic wave absorption according to claim 1, characterized in that: In step (3), the drying temperature is 60-70° C. and the drying time is 12-24 h; The heating rate of the second stage is 5-7°C / min.

6. A ternary composite nanofiber that can be used for marine metal corrosion protection and electromagnetic wave absorption, characterized in that: The method is prepared by any one of claims 1 to 5.

7. A coating that can be used for marine metal corrosion protection and electromagnetic wave absorption, characterized in that: The invention comprises a resin, a curing agent, a second solvent and a ternary composite nanofiber as claimed in any one of claims 1 to 6 and can be used for marine metal corrosion protection and electromagnetic wave absorption.

8. The coating for marine metal corrosion protection and electromagnetic wave absorption as claimed in claim 7, characterized in that: The resin is an epoxy resin, the curing agent is a polyamide curing agent, and the mass ratio of the epoxy resin to the polyamide curing agent is 1:(0.5-1.2); The second solvent is ethanol, and the mass ratio of epoxy resin to ethanol is 1:(1.5-2.1); The mass ratio of the ternary composite nanofibers that can be used for marine metal corrosion protection and electromagnetic wave absorption to the epoxy resin is 1%-5%.

9. A coating that can be used for marine metal corrosion protection and electromagnetic wave absorption, characterized in that: The coating layer is formed by drying the coating material according to claim 7 or 8.

10. A marine engineering component with dual functions of corrosion protection and electromagnetic wave absorption, characterized in that: It comprises a metal substrate, the surface of which is loaded with the coating as claimed in claim 9.

Citation Information

Patent Citations

  • Fe-Co alloy / C composite nanofiber microwave absorbent, and preparation method and application thereof

    CN103422192A

  • Cu-MnO / carbon nanometer fiber composite material and preparation method and application thereof

    CN110085447A

  • CeO2 / Co / C nano composite fiber material as well as preparation method and application thereof

    CN116876113A

  • Method of synthesizing carbon nanofiber using cobalt-copper based catalyst and carbon nanofiber synthesized thereby

    KR101452728B1

  • Eco-friendly Steel Coating Method with Improved Salt-resistance and Anti-fouling Properties

    KR102701300B1

Cited By

  • Composite material and preparation method thereof

    CN121182146A